Perbedaan Tingkat Kecemasan Antara Investor dan Trader Dalam Menghadapi Penurunan Harga di Pasar Modal Indonesia - Regi, Muhamad (EDU SOCIATA ( JURNAL PENDIDIKAN SOSIOLOGI ), 2025)
This study aims to investigate differences in anxiety differences in anxiety levels between investors and traders in Indonesia’s capital market during stock price declines. Using a quantitative comparative approach, data were collected from 502 respondents (251 investors and 251 traders) through purposive sampling and analyzed using an independent samples t-test. Results showed a significant difference in anxiety levels between investors (M = 51.04) and traders (M = 56.25), with a p-value of 0.000 (<0.05). Most investors (74.9%) and traders (62.9%) experienced moderate anxiety levels, but traders had a higher proportion of high anxiety (33.1%) compared to investors (13.1%). This indicates that short-term trading activities impose greater psychological pressure than long-term investing. The findings support Greenberger and Padesky’s (2016) cognitive-behavioral theory, which explains anxiety as an interaction of thoughts, emotions, behaviors, and physical symptoms. This study highlights the importance of psychological education and stress management strategies for market participants, particularly traders, to maintain mental well-being and sound decision-making in volatile markets.